Teacher Strategies in Fostering Behavior Learners on The Use of Gadgets as Social Media - Muhajir, Syamsul; Maslikhah, Maslikhah (Jurnal Penelitian Pendidikan, 2025)
The purpose of this study is 1) The use of social media through gadgets at MI Nuril Huda Losari, Sumowono District, Semarang Regency. 2) The development of student behavior in the use of social media through gadgets towards changes in children's behavioral personality. 3) Teacher strategies in anticipating the development of the use of social media through gadgets towards changes in children's behavioral personality. This research is a qualitative research with data collection methods using observation, interviews. The object of research at MI Nuril Huda Sumowono, Semarang Regency. The results of the study are that the development of social media use through gadgets is very significant, almost all upper-class students are able to use social media, but there is a lack of parental involvement in supervising children's gadget use. The impact of the development of social media use through gadgets is, Facilitating communication, Expanding friendship networks or getting new friends, Making it easier to find information, For learning access, Social media can be used as a means of entertainment when finishing homework or schoolwork, Social media can stimulate children to follow current technological developments, or so that children are not gaptek (technologically illiterate). The negative impact is, it can cause a sense of dependence in children because when they operate the application on their gadgets they forget the time and even postpone activities that they should be doing but they are busy playing gadgets, Messy sleep patterns, Eye disorders due to exposure to radiation due to often staring at the gadget screen they are holding. The concept of teachers in preventing the negative impacts of social media use on students is as follows: a.) Teachers become role models imitated by students so that what is prohibited and recommended by teachers is carried out voluntarily because the teachers they imitate also do the same thing. Teachers must set a good example by following the development of the times in a healthy and reasonable manner even though it is related to the development of science and technology today. b.) Teachers provide motivation to students, as the duties and roles of a teacher, a teacher must provide motivation or advice that builds positive behavior or good morals and good achievements by following the development of the times in a healthy and reasonable manner even though it is related to the development of science and technology today.